Fintech and the socialization of the financial industry - Miguel, A. F. (2020)
Fintech have known an incredible exposure over the last years, attracting investments of large billions of dollars. Fintech are the match between finance and technology and they are imposing a new way of thinking in all the branches of the financial industry. After the financial crisis of 2008, people have changed their way of seeing “Finance” and, more particularly, the role of banks, looking for products and services that correspond to their needs. Moreover, the financial crisis has highlighted a relevant number of dysfunctions on the banking sector and on the financial regulation. Regulators have strengthened their requirements for banks, particularly in their relations with clients. These have opened a breach for Fintech companies and they are using it. Fintech companies rely on a different value proposition to clients that is based on a timesaving, fast and clear experience. Indeed, they propose major innovations in products and processes. Fintech companies put the client back at the center of all their attention and clients are now the top priority.